Syphilis among Female Sex Workers: Results of Point-of-Care Screening during a Cross-Sectional Behavioral Survey in Burkina Faso, West Africa. (8th November 2018) - Ouedraogo, Henri Gautier; Meda, Ivlabehire Bertrand; Zongo, Issaka; Ky-Zerbo, Odette; Grosso, Ashley; Samadoulougou, Benoit Cesaire; Tarnagda, Grissoum; Cisse, Kadari; Sondo, Apoline; Sawadogo, Nongoba; Traoré, Yves; Barro, Nicolas; et al.
Abstract : Background . Syphilis among female sex workers (FSW) remains a public health concern due to its potential impact on their health and the possibility of transmission to their clients, partners, and children. Recent data on the prevalence of syphilis in the population in West Africa are scarce. The objective of this study was to measure the seroprevalence of syphilis serological markers among female sex workers in Burkina Faso. Methods . We conducted a cross-sectional survey among FSW between February 2013 and May 2014. Participants were recruited using respondent-driven sampling (RDS) methods in five cities of Burkina Faso (Ouagadougou, Bobo-Dioulasso, Koudougou, Ouahigouya, and Tenkodogo). FSW were enrolled and screened for syphilis using a syphilis serological rapid diagnostic test. Data from all cities were analyzed with Stata version 14.0. Results . A total of 1045 FSW were screened for syphilis. Participants' mean age was 27.2 ± 0.2 years. The syphilis serological markers were detected in 5.6% (95% CI: 4.4–7.2) of the participants whereas active syphilis was seen in 1.4% (95% CI: 0.9–2.4). RDS weighted prevalence of syphilis serological markers and active syphilis by city were, respectively, estimated to be 0.0% to 11.0% (95% CI: 8.1–14.7) and 0.0% to 2.2% (95% CI: 1.1–4.4). No syphilis markers were found among Ouahigouya FSW. Low education level and high number of clients were factors associated with syphilis markers among the FSW. Conclusion . The prevalence of syphilis markers was high during this study among FSW. This highlights the need to reinforce the comprehensive preventive measures and treatment of syphilis in this population.